2021
DOI: 10.17478/jegys.846480
|View full text |Cite
|
Sign up to set email alerts
|

The effects of using games on teaching vocabulary in reading comprehension: a case of gifted students

Abstract: Using educational games for the improvement of the students' vocabulary retention has been widely used in the educational setting for many decades. The acquisition of vocabulary as part of the subskills of the English language is considered a vital part of learning any target language. Hence, this research study aimed at exploring the effects of using games to teach vocabulary in reading comprehension among freshmen students at Takhar University. This study has employed mixed-method research involving pre-test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
1
14
0
1
Order By: Relevance
“…The findings of the study indicated no significant impact on students' attitudes towards learning English vocabulary, idioms, and phrases. Another study carried out by Hashemi (2021) who investigated the effects of using games on teaching vocabulary in reading comprehension. He found in his study that teaching vocabulary in reading comprehension can help students in their skills.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The findings of the study indicated no significant impact on students' attitudes towards learning English vocabulary, idioms, and phrases. Another study carried out by Hashemi (2021) who investigated the effects of using games on teaching vocabulary in reading comprehension. He found in his study that teaching vocabulary in reading comprehension can help students in their skills.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…This study established a positive relationship between gaming videos and academic achievement when the videos were used as part of learning. They attributed this to technology's ability to provide learning, fun, and motivation (Hashemi 2021). In addition, they attribute the high academic achievement to the interactive nature of technology mimicking a self-driven practical learning approach.…”
Section: Effects Of Technology On English Learningmentioning
confidence: 99%
“…Anak yang berada pada tahap ini sangat memerlukan adanya alat bantu yang dapat ia gunakan dalam memahami konsep yang masih bersifat abstrak (Arini & Lovisia, 2019;Puspaardini et al, 2019). Maka dari itu pengembangan perangkat pembelajaran ini dapat membantu siswa dalam memahami atau membantu siswa dalam mengikuti pembelajaran dengan baik (Arinda et al, 2019;Hashemi, 2021).…”
Section: Pembahasanunclassified